Water & wastewater: Los Angeles water reclamation plant selects innovation. Issue 5 (September 2015) - Unknown
Abstract : As California faces one of the most severe droughts on record, water reuse is an essential and sustainable solution that will help secure the state's water needs. This article sees how Xylem has been commissioned to deliver a unique water reuse solution to help increase the supply of purified, recycled water in Los Angeles.